2016
DOI: 10.2147/ppa.s105241
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction among men with concurrent benign prostatic hyperplasia and erectile dysfunction treated with tadalafil or other phosphodiesterase type-5 inhibitor combinations

Abstract: ObjectiveErectile dysfunction (ED) and benign prostatic hyperplasia (BPH) frequently co-occur in men aged ≥40, along with lower urinary tract symptoms (LUTS) secondary to BPH. Given little real-world evidence on treatment use or satisfaction with treatment for concurrent BPH/LUTS and/or ED, this study examined medication regimens and differences in satisfaction and health-related quality of life (HRQoL) across regimens among men with concurrent BPH and ED.MethodsA cross-sectional study was conducted using an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Lastly, a cross‐sectional survey was included. Tadalafil monotherapy scored significantly higher on patient satisfaction and convenience than tadalafil combined with α‐blockers and/or 5α‐reductase inhibitors (5‐ARIs) [ 15 ] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, a cross‐sectional survey was included. Tadalafil monotherapy scored significantly higher on patient satisfaction and convenience than tadalafil combined with α‐blockers and/or 5α‐reductase inhibitors (5‐ARIs) [ 15 ] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding patient satisfaction, Lee et al [15] conducted an internet survey of 507 men with both ED and BPH.…”
Section: Discussionmentioning
confidence: 99%
“…The least wanted undesirable effect was ejaculatory dysfunction (retrograde or diminished ejaculation), which is a well-known side effect of selective ABs [ 70 ]. This has previously been shown to be the main factor associated with high satisfaction in the tadalafil only group compared with the PDE5-I combination or tadalafil combination groups (both of which include the use of ABs) [ 71 ]. In our study, 9 patients in the CT group (tadalafil + tamsulosin) discontinued due to ejaculatory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The most common undesirable effect was ejaculatory dysfunction, a well-known side effect of selective α-blockers [20]. This has previously been shown to be the main factor related to low satisfac-tion with combination treatment using α-blockers and PDE5 inhibitors [21]. However, other adverse events related to tadalafil may have less impact on treatment persistence, based on previous studies with once-daily tadalafil that reported discontinuation rates due to the side effect as low as 1% to 6% [22][23][24].…”
Section: Treatment Persistence With a Fixed-dose Combinationmentioning
confidence: 99%